Peran Aparat Pemerintahan Desa Dalam Mewujudkan Pengelolan Keuangan Desa Yang Efektif Terhadap Pembangunan - Purba, Sri Damar Wulan Yasinta; Kartika, Indri; Sitanggang, David Christian; Saragih, Johan Perdana; Herdiansyah, Habib Akbar; Sitorus, Novandiwan; Ivanna, Julia (Journal of Law & Policy Review, 2023)
Village development is a process of activities carried out by all village components to incrase community empowerment in achieving prosperity. To create a properous village, effective management of village funds is needed. Effective village financial management can be achieved if the management of village income, village expenditure, and village financing is carried out based on transparent, ccountable and participatory principles and is carried out in an orderly and disciplined budget. The most influential organ to carry out these objectives is the village government apparatus consisting of the village head and assited by village officials such as the village secretariat, regional administrators and technical implementers who are the elements of village administrators. This article aims to determine the role of village government officials in managing village finances and to find out the effectiveness of village financial management. This article uses the literature study method. Therefor, village government planning and budgeting, implementation, administration, reporting, and accountability stages by apllying the four principles mentioned in Permendagri No. 113 of 2014.